2021
DOI: 10.2196/24429
|View full text |Cite|
|
Sign up to set email alerts
|

General Audience Engagement With Antismoking Public Health Messages Across Multiple Social Media Sites: Comparative Analysis

Abstract: Background Public health organizations have begun to use social media to increase awareness of health harm and positively improve health behavior. Little is known about effective strategies to disseminate health education messages digitally and ultimately achieve optimal audience engagement. Objective This study aims to assess the difference in audience engagement with identical antismoking health messages on three social media sites (Twitter, Facebook,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…The studies by Kite et al [ 56 ], Lister et al [ 57 ], Parackal et al [ 58 ], Rabarison et al [ 59 ], and Reuter et al [ 60 ] measured engagement in and of itself. In particular, the study by Rabarison et al [ 59 ] focused on a specific aspect of the social media in question: Twitter chats.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies by Kite et al [ 56 ], Lister et al [ 57 ], Parackal et al [ 58 ], Rabarison et al [ 59 ], and Reuter et al [ 60 ] measured engagement in and of itself. In particular, the study by Rabarison et al [ 59 ] focused on a specific aspect of the social media in question: Twitter chats.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, chats of this kind should be used as an engagement tool with the audience by sharing messages and responding to questions from the public. Focusing on Twitter, Instagram, and Facebook, Reuter et al [ 60 ] concluded that engagement with a health message on social media does not indicate user engagement on a website and, therefore, it is recommended that both metrics be taken into account when designing health promotion strategies. It was also suggested to combine organic and advertising messages in health promotion campaigns.…”
Section: Resultsmentioning
confidence: 99%
“…We need more information about which platforms and channels are most likely to drive people to such websites and which are best at capturing the types of people who will engage with the website content. One recent study43 indicated that the social media platform that had the best click-through rate had the least effective website engagement rate.…”
Section: Campaign Reachmentioning
confidence: 99%
“…There is existing evidence that there are some differences between age groups across the lifespan about how public health information is accessed and used in general ( 19 ). There are also differences in engagement when comparing different social media modes of disseminating public health information ( 20 ). However, there is relatively little research relating to differences between age groups and health messaging specifically relating to the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%